Shock effects of underwater explosion on naval ship foundations: Validation of numerical models by dedicated tests. (1st June 2022) - Mannacio, F.; Barbato, A.; Di Marzo, F.; Gaiotti, M.; Rizzo, C.M.; Venturini, M.
Abstract: The underwater shock explosions can cause severe damage not only to the naval ships machinery and equipment, but also to their foundation structures, that are a critical part of the system integration. A few national rules allow shock resistance verification by means of dedicated calculations as it is in general not possible the testing of the complete system machine-foundation. Dynamic structural analysis of foundations by Finite Element Method (FEM) is accepted, but no detailed modelling strategies, procedures and inputs are provided. The aim of this paper is to provide some reliable guidelines of shock foundation design, comparing the results obtained by the numerical simulation with the experimental data collected performing a series of dedicated shock tests carried out according to the MIL S 901 D medium weight shock standard. Eventually, it is shown that experimental and numerical analyses performed in parallel may support each other to provide better understanding of complex phenomena. Highlights: Underwater explosions can be severe not only for machinery but also for foundations. In early design phase testing equipment with foundations is generally not possible. No detailed modelling strategies are provided by rules for scantling assessment. Dynamic implicit Finite Element analysis is validated by dedicated shock tests. Experimental + numerical analyses give better understanding of such complex phenomena.